Computational Metallurgy: Advent of Cross‐Scale Modeling: High‐Performance Computing of Solidification and Grain Growth (Adv. Theory Simul. 9/2018). Issue 9 (6th September 2018) - Shibuta, Yasushi; Ohno, Munekazu; Takaki, Tomohiro
Abstract : The application range of computational metallurgy is rapidly expanding thanks to recent progress in high‐performance computing. In article number1800065, Yasushi Shibuta and co‐workers introduce state‐of‐the‐art collections of large‐scale simulations of solidification and grain growth performed on the GPU supercomputer. These simulations are now bridging the gap between atomistic and continuum‐based simulations, which creates new criteria for multi‐scale modeling.